The prognostic and predictive value of AFP in immune checkpoint inhibitor-treated hepatocellular carcinoma: a systematic review and meta-analysis - Tian, Bao-Wen; Yan, Lun-Jie; Liang, Wei-Chao (Frontiers in Immunology, 2025)
IntroductionAlpha-fetoprotein (AFP) is a universally recognized tumor marker in hepatocellular carcinoma (HCC). Its utility in assessing the response to immune checkpoint inhibitors (ICIs) remains controversial. This study aims to investigate the predictive value of AFP in ICIs-treated HCC patients.MethodA systematic search strategy was deployed across the PubMed, Embase, Cochrane Library and Web of Science databases. Hazard ratios (HR) or odds ratios (OR) and the corresponding 95% confidence intervals (CIs) were used to assess the pooled risk.ResultThe study encompassed a total of 131 studies. Overall survival (OS) (HR = 1.60, 95%CI=1.47-1.74), progression-free survival (PFS) (HR = 1.35, 95%CI=1.27-1.42), and disease control rate (DCR) (OR = 0.50, 95%CI=0.29-0.84) were poorer in ICIs-treated patients with high AFP levels than those with low AFP levels. However, AFP levels were not associated with the objective response rate (ORR) (OR = 0.96, 95%CI=0.74-1.24). In addition, patients who achieved an AFP response had favorable OS (HR = 0.41, 95%CI=0.33-0.52), PFS (HR = 0.38, 95%CI=0.30-0.47), ORR (OR = 5.39, 95%CI=3.96-7.32) and DCR (OR = 5.48, 95%CI=3.71-8.11). Subgroup analyses revealed that AFP>400ng/ml and AFP decline greater than 20% were the most used and efficient cut-off values for high AFP level and AFP response, respectively.ConclusionHigh AFP levels are associated with worse outcomes in ICIs-treated HCC. The assessment of AFP response demonstrated promising predictive value for both prognosis and therapeutic response to ICIs. Accurately defining early AFP response remains an area that requires further investigation.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD-42024606729.